1978
DOI: 10.2337/diacare.1.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Jet Injection of Insulin During Self-Monitoring of Blood Glucose

Abstract: Insulin-dependent diabetes mellitus has been treated with four jet injections of insulin (regular insulin before each meal and intermediate insulin at bedtime) during self-monitoring of blood glucose levels. The blood glucose levels generally remain within 60 and 150 mg/dl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 4 publications
0
18
0
1
Order By: Relevance
“…In a similar sized study cohort ( n = 69), half of the patients had capillary blood glucose profiles in which no more than one value exceeded 10.0 mmol/l [4]. Other, albeit smaller, studies confirmed these results [5][6][7].…”
Section: Bernstein's Diabetes Solution: a Complete Guide To Achievingmentioning
confidence: 74%
“…In a similar sized study cohort ( n = 69), half of the patients had capillary blood glucose profiles in which no more than one value exceeded 10.0 mmol/l [4]. Other, albeit smaller, studies confirmed these results [5][6][7].…”
Section: Bernstein's Diabetes Solution: a Complete Guide To Achievingmentioning
confidence: 74%
“…It was used for the first blood glucose meter in 1970 (15). Starting in the late 1970s, daily BGM gained wider acceptance as research data began to support the correlation and causation between poor glycemic control and diabetic complications (15)(16)(17)(18)(19)(20)(21)(22)(23). The "glucose hypothesis" was confirmed in the landmark Diabetes Control and Complications Trial (DCCT), the first longterm randomized prospective study to compare intensive (≥4x/day) self-GM coupled with an insulin titration algorithm versus standard therapy using once-daily GM and 1 to 2 daily insulin injections (24).…”
Section: History Of Gm In Diabetesmentioning
confidence: 99%
“…To ease the burden of multiple injections, the patients administered the insulin by jet spray (Mizzy Syrijet Mark II). 3 ' 4 The patients, under the guidance of the physicians, nurses, and manufacturer's representatives who indoctrinated them in the use of the instruments, attempted to maintain the fasting levels of glucose between 50 and 150 mg/dl and day and evening levels between 50 and 180 mg/dl while on their usual ADA diet. The results of the initial urine and blood tests in nine of these patients have been published.…”
Section: Methodsmentioning
confidence: 99%